2015
DOI: 10.1556/achrom.27.2015.4.9
|View full text |Cite
|
Sign up to set email alerts
|

UPLC/Q-TOF-MS Analysis for Identification of Hydrophilic Phenolics and Lipophilic Diterpenoids from Radix Salviae Miltiorrhizae

Abstract: Summary.A rapid method has been used for simultaneous identification of both hydrophilic and lipophilic compounds from Radix Salviae Miltiorrhizae (RSM, the root of Salvia miltiorrhiza B GE .) by ultra-performance liquid chromatography/quadrupole time-offlight mass spectrometry (UPLC/Q-TOF-MS). A total of 58 compounds extracted by methanol were detected and tentatively identified within 20 min, including hydrophilic phenolics, lipophilic diterpenoids, a verbascose, and several organic acids. These compounds we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(18 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…In addition to caffeic acid (peak 3) and rosmarinic acid (peak 21) this research has shown the presence of ten other caffeic acid esters (peaks 1,7,15,19,22,24,25,27,30,34) known as lithospermic acids or salvianolic acids. Caffeic acid, rosmarinic acid, lithospermic acid A (peak 22), and lithospermic acid B (peak 24) were identified using authentic standards or herbal reference materials (Salvia miltiorrhiza Bunge, Melissa officinalis L.) and literature data [32,34,35].…”
Section: Resultsmentioning
confidence: 90%
“…In addition to caffeic acid (peak 3) and rosmarinic acid (peak 21) this research has shown the presence of ten other caffeic acid esters (peaks 1,7,15,19,22,24,25,27,30,34) known as lithospermic acids or salvianolic acids. Caffeic acid, rosmarinic acid, lithospermic acid A (peak 22), and lithospermic acid B (peak 24) were identified using authentic standards or herbal reference materials (Salvia miltiorrhiza Bunge, Melissa officinalis L.) and literature data [32,34,35].…”
Section: Resultsmentioning
confidence: 90%
“…Applying the optimized LC–MS conditions, samples of the seven medicinal herbs were analyzed and typical base peak ion chromatograms are shown in Figure S1. Comparing the MS spectra with standards and literature data (Chen et al, ; Chen, Qi, Chang, Zhu, & Yu, ; Hong, Wang, Xu, Li, & Li, ; Liang et al, ; Liu et al, ; Ma et al, ; Si et al, ; Yang et al, ; Yang, Wu, Rui, Guo, & Feng, ; Yi, Leung, Lu, Chan, & Zhang, ), a total of 134 chemical constituents were identified in the seven medicinal herbs, and their information is summarized in Tables S1–S7. Among these, 31 compounds in Salviae Miltiorrhizae were mainly salvianolic acids and diterpene quinones, 16 compounds in Radix Angelica Sinensis and 26 compounds in Rhizoma Chuanxiong were mostly phenolic acids and phthalides, three compounds in Semen Persicae were mainly cyanogenic glycosides, 16 compounds in Flos Carthami and 18 compounds in Fructus Aurantii were largely flavonoids, and 24 compounds in Radix Bupleuri were mostly triterpenoid saponins.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 35 salvianolic acids were identied, of which ve compounds (danshensu, lithospermic acid, salvianolic acid A, salvianolic acid B and rosmarinic acid) were unambiguously identied by comparing their retention times, accurate molecular masses and MS/MS fragments with those of the standard references; moreover, the remaining 30 compounds were tentatively identied by comparing their exact molecular masses, fragmentation information, retention times and dri times with previously reported values. [32][33][34] Identication of astragalosides in DZT. Most of the astragalosides contain the same tetracyclic triterpenoids , corresponding to the aglycone and successive losses of water molecules; thus, these ions can help us identify as many astragalosides as possible.…”
Section: Resultsmentioning
confidence: 99%